Analysis of stress in sputter-deposited films using a kinetic model for Cu, Ni, Co, Cr, Mo, W - Su, Tong; Rao, Zhaoxia; Berman, Sarah; Depla, Diederik; Chason, Eric (Applied surface science, 2023)
[Display omitted] •A kinetic model explains and predicts residual stress evolution during deposition of sputtered and evaporated metallic thin films.•The model includes stress generation from deposition processes, grain growth and energetic particle bombardment.•The model is used to analyze six metallic thin films (Cu, Ni, Co, Cr, Mo, W) deposited under an array of deposition conditions. Many published studies have quantified film stress evolution for different processing conditions and deposition methods. Here, data from multiple wafer curvature measurements in the literature (for evaporated and sputter-deposited Cu, Ni, Co, Cr, Mo and W) are analyzed in terms of a kinetic model to develop a comprehensive picture of the processes that control film stress. The model includes the effects of film growth kinetics, grain growth and incoming particle energy. Non-linear least squares fitting of the data to this model enables the determination of kinetic parameters that control the stress for each material. The fitting for each material is done in a way that optimizes the parameters simultaneously for all the measurements, both sputtered and evaporated. Parameters that depend only on the material are constrained to have a common value among all the data sets for that material. The validity of the resulting parameters is evaluated by comparing with values estimated from the underlying physical mechanisms.